Current Evidence of Probiotics in Pediatrics with Short Bowel Syndrome, Is It Safe and Beneficial? A Literature Review - Andhary, Vianca Samara; Razan, Rafi Alfian; Partiwi, I Gusti Ayu Nyoman (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: Short Bowel Syndrome (SBS) presents significant challenges in pediatric care, particularly due to its high incidence in neonates and the associated health burdens, including elevated mortality rates primarily from hepatic failure and sepsis. SBS in infants and young children primarily arises from congenital defects or acquired conditions that necessitate significant bowel resection. The predominant cause of SBS during the neonatal period is necrotizing enterocolitis (NEC), accounting for 35% to 50% of cases. In older children, SBS is frequently associated with midgut volvulus or traumatic injuries. Discussion: Managing pediatric SBS requires a multidisciplinary approach that involves evaluating dietary, pharmacology, and surgical factors. Key strategies focus on improving absorptive capacity, promoting intestinal adaptation, and regulating bowel motility. In infants and young children, SBS often leads to a range of complications, including nutrient deficiencies, fluid imbalances, and growth delays. The condition necessitates careful medical management to address these challenges and promote optimal health outcomes. Recent studies have investigated probiotics as an adjuvant treatment for SBS, demonstrating enhanced growth, nutritional status, and inhibition of harmful microbes in afflicted children Conclusion: The use of probiotics in children with SBS has shown both safety and beneficial effects, making it a feasible alternative therapy in routine medical practice. However, the lack of significant clinical data highlights the need for more study to better understand the efficacy of probiotics in the treatment of SBS.